All Different, Yet All the Same? The Place of New Parties in Lithuanian Party System - Skirkevičius, Paulius (Politologija, 2021)
One of the prominent feature of the Lithuanian party system is constant success of new parties. Based on political parties’ programmatic stances, this article investigates the place of these new parties in the Lithuanian party system. Using three different metrics (place in two-dimensional political spectrum, programmatic differences, nicheness), article aims at locating new parties in the party system as well as finding common denominators in party programmatic stances, which could let to assign new parties to the specific type of political parties. Analysis reveals that even though one cannot say, that all new parties are totally the same, there are common features that defines these parties (central position in the political spectrum, lack of clear programmatic niche, stressing common political issue, which separates them from traditional parties).